Literature Review: Personal Hygiene for Patients after Laparotomy - Puji Triyanto; Dwi Retno Sulistyaningsih; Suyanto Suyanto; Dwi Heppy Rochmawati (Indonesian Journal of Global Health Research, 2025)
Personal hygiene care in post-laparotomy patients is very important to accelerate the healing process and prevent infection. Good hygiene is associated with a reduced risk of post-operative complications. The purpose of this study was to analyze the effect of personal hygiene on the recovery of post-laparotomy patients and the factors that influence it. This study utilized a Systematic Literature Review design, adhering to the PRISMA guidelines. The search for relevant articles was conducted across two primary scientific databases, SINTA and Scopus, covering the publication period from 2020 to 2025. The search strategy was formulated using a combination of keywords: "Infection Prevention," "Personal Hygiene," "Post-Laparotomy," and "Wound Healing." This initial search resulted in 860 articles. The selection process was carried out in two main stages: an initial screening to remove duplicates and irrelevant articles based on their titles and abstracts, followed by a full-text review of articles that met the predefined inclusion criteria. Consequently, articles that did not satisfy the exclusion criteria were removed from the review. Through this rigorous process, a total of 15 relevant articles were selected for in-depth analysis. The results showed that personal hygiene, including wound care and overall body hygiene, had a significant impact on wound healing and reducing post-operative infections. Family support and adequate education about personal hygiene also played an important role in the recovery of post-laparotomy patients.